INTEGRATING ARABIC CALLIGRAPHY INTO TSANGAYA SYSTEM OF EDUCATION IN MAIDUGURI FEASIBILITY ASSESSMENT AND SOCIAL ACCEPTANCE - Abba Alhaji Bukar, Abubakar Shettima Mohammed Bukar (Spektra: Jurnal Ilmu-ilmu Sosial, 2025)
This study examines the integration of Arabic calligraphy into Tsangaya education in Maiduguri, focusing on the perceptions and readiness of key stakeholders teachers, learners, and parents/community leaders. A total of 258 respondents participated, comprising 45 teachers, 150 learners, and 63 parents. Data were collected using structured questionnaires and analyzed using descriptive statistics and inferential tests. Findings show that 73.3% of teachers believe Arabic calligraphy adds value to Tsangaya education, while 73.3% are willing to undergo training to teach it. Among learners, 76.6% expressed interest in learning calligraphy, and 80% agreed it would improve their Arabic writing skills. Additionally, 84.2% of parents supported its inclusion in the curriculum, citing cultural and religious significance. However, challenges were identified: only 38.8% of respondents believed there are enough qualified teachers, and 41.9% cited lack of teaching materials as a barrier. A one-way ANOVA revealed a statistically significant difference in stakeholder views (F = 4.67, p = 0.011), with Scheffé post hoc analysis indicating that learners held significantly more favorable views than teachers. The study concludes that while Arabic calligraphy is widely supported and seen as beneficial, successful implementation will require strategic investment in teacher training, curriculum adaptation, and resource provision. These findings offer comprehensive and valuable recommendations for policymakers and educators aiming to enrich Tsangaya education through culturally relevant skills.